The Higher Moments of Future Earnings - Chang, Woo-Jin; Monahan, Steven J.; Ouazad, Amine; Vasvari, Florin P. (The Accounting Review, 2021)
ABSTRACT We evaluate whether reported accounting numbers are informative about earnings uncertainty and whether earnings uncertainty is priced. We use quantile regressions to forecast the standard deviation, skewness, and kurtosis of future earnings. These three moments are important measures of earnings uncertainty because they reflect the size of the average deviation from expected earnings and the amount of extreme upside potential, extreme downside risk, or both. We develop a novel approach for evaluating the reliability of our forecasts and we show that they are reliable. We also document that: (1) equity prices are increasing (decreasing) in the standard deviation and skewness (kurtosis) of lead return on equity and (2) credit spreads are increasing (decreasing) in the standard deviation and kurtosis (skewness) of lead return on assets. Our results indicate that historical financial statements are informative about earnings uncertainty and that earnings uncertainty is priced. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: C21; C53; G17; M41.